2019
DOI: 10.1016/j.pmrj.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors Among Older Adults With Long‐Term Spinal Cord Injury

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…In agreement with previous population-based studies of persons with SCI of different ages [1,18], we found that LTPA participation varied greatly, and many of the older adults did not engage in any LTPA [17]. Also, we have recently reported on a high occurrence of cardiovascular risk factors in the same Swedish SCI-sample [19]. In that study, we found only weak associations between the occurrence of risk factors and non-modifiable sociodemographics and injury characteristics [19].…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…In agreement with previous population-based studies of persons with SCI of different ages [1,18], we found that LTPA participation varied greatly, and many of the older adults did not engage in any LTPA [17]. Also, we have recently reported on a high occurrence of cardiovascular risk factors in the same Swedish SCI-sample [19]. In that study, we found only weak associations between the occurrence of risk factors and non-modifiable sociodemographics and injury characteristics [19].…”
Section: Introductionsupporting
confidence: 91%
“…Also, we have recently reported on a high occurrence of cardiovascular risk factors in the same Swedish SCI-sample [19]. In that study, we found only weak associations between the occurrence of risk factors and non-modifiable sociodemographics and injury characteristics [19]. Further studies are therefore needed to increase our knowledge about modifiable factors associated with the specific cardiovascular risk profile of older adults with long-term SCI.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The results from our previous cross-sectional studies are overall positive, showing that these older adults with long-term SCI exhibit a relatively high level of physical independence, are generally satisfied with their lives, have a strong sense of coherence and a low presence of probable depression. However, our results also provide indications for a proactive approach in clinical follow-up, especially regarding pain, depressive symptoms, satisfaction with sexual life, and lifestyle-related factors [17][18][19][20][21].…”
Section: Methodsmentioning
confidence: 62%